Cytokine profile in tear and aqueous humor of primary open-angle patients as a prognostic factor for trabeculectomy outcome. Issue 5 (September 2022) - Burgos-Blasco, Barbara; Vidal-Villegas, Beatriz; Saenz-Frances, Federico; Fernandez-Vigo, Jose I; Andres-Guerrero, Vanessa; Espino, Laura; Garcia-Feijoo, Julian; Martinez-de-la-Casa, Jose M
Objective: To evaluate the cytokine profile in tear and aqueous humor in primary open-angle glaucoma before trabeculectomy and correlate preoperative cytokine levels with the surgical outcome. Methods: Prospective study. Twenty-nine patients with primary open-angle glaucoma undergoing primary trabeculectomy were included. Levels of 27 cytokines were measured in tear an aqueous humor using the Bio-Plex Pro Human Cytokine 27-Plex Immunoassay kit (Bio-Rad Laboratories, Hercules, CA, USA). Results: 29 patients who underwent trabeculectomy were included and their first-year follow-up visits were recorded. Mean age was 76.0 ± 7.0 years (range 56–84), mean intraocular pressure was 18.2 ± 3.6 mmHg and mean number of topical medications was 2.3 ± 0.9. At the one-year visit, 5 patients were classified as surgical failure. In aqueous humor, preoperative cytokine levels of regulated on activation normal T cell expressed and secreted (RANTES) were significantly higher in those patients with surgical failure at one year. IL-8 in tear and interferon gamma-induced protein (IP-10) in aqueous humor correlated positively with one-year IOP reduction. No statistically significant correlations were found with changes in visual field mean defect or global peripapillary retinal nerve fiber layer thickness (all, p >0.05). Conclusions: Preoperative RANTES levels in aqueous humor as well as other cytokines could serve as useful biomarkers for trabeculectomy outcome.